HEREDITARY HEMOLYTIC ANEMIA β -THALASSEMIA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Hereditary hemolytic anemia and beta-thalassemia are blood disorders that affect the process of hemoglobin production in the human body. These diseases are mainly related to genetic factors, and their prevalence and appearance depend on many factors. In this article, we will review the biological basis, clinical manifestations, diagnosis and treatment methods of these diseases.